Extrınsıc motıvatıon orıentatıon аs a predıctor of ımpressıon management among academıcs ın Istanbul, Turkey - Khadyr, Amıne (My University, 2016)
Bu araştırmanın amacı, Türkiyedeki Akademisyenlerin, iç ve dış kaynaklı güdülenme yönelimleri ile çevreleri ile olan ilişkilerinde kullandıkları etkileme taktikleri arasındaki ilişkiyi anlamaktır. Bu bağlamda, Güdülenme yönelimleri doğrultusunda iki gruba ayrılan akademisyenlere, Jones and Pittman’ın geliştirmiş oldukları birtakım etkileme taktiklerini, çalışma hayatlarında ne sıklıkla kullandıkları sorulmuştur. Kullanılan etkileme taktiklerine göre iki grup karşaılaştırıldığında, dış kaynaklı güdülenme yönelimi yüksek akademisyemlerin, iç kaynaklı güdülenme yönelimleri yüksek akademisyenlere göre, manidar düzeyde yüksek cevaplar verecekleri temel varsayımımızı oluşturmaktadır. zlenim yönetimi, dışsal motivasyon, içsel motivasyon, akademisyenler

Nowadays, it has become crucial to understand why individuals behave in the way they do, and what are the motives behind those behaviors. The main purpose of this research is to investigate the relationship between extrinsic and intrinsic motivation and impression management among academics in Turkey. It is expected that extrinsically motivated academics would be more likely to use impression management whereas intrinsically motivated academics would score less in usage of impression management. Academics from different universities of Turkey were surveyed by theory based intrinsic and extrinsic motivation questionnaire and Jones and Pittman taxonomy based impression management scale. The importance of this study lies on understanding the impression management behaviors of academics by how much and what kind (ingratiation, exemplification and self promotion) of impression management strategies they used and with what reasons. Key words: impression management, extrinsic motivation, intrinsic motivation, academics
Keywords: İşletme; Yönetim